PERBEDAAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MENGGUNAKAN LEGO DI TK SWASTA KEMALA BAYANGKARI - Juhemi Kespensia Sirait; Isa Hidayati (STKIP Subang, 2026)
Fine motor skills are essential for supporting learning readiness in early childhood; however, some children aged 5–6 years still experience difficulties in activities requiring hand and finger coordination, such as cutting, pasting, and holding writing tools properly. his study aimed to investigate the effect of LEGO play activities on the fine motor skills of children aged 5–6 years. A quantitative method with a One-Group Pretest–Posttest design was employed involving 10 children in Group B at Kemala Bhayangkari Kindergarten, Kabanjahe, Karo Regency. Data were collected through an observation instrument consisting of eight indicators of fine motor development and analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed a significant improvement in children's fine motor abilities after participating in LEGO-based activities. The mean score increased from 19.1 in the pretest to 28.1 in the posttest, representing a gain of 9 points. Statistical analysis revealed a significance value of 0.005 (p < 0.05), indicating a significant difference between pretest and posttest scores. These findings demonstrate that LEGO play is an effective educational tool for enhancing fine motor development and can be incorporated into early childhood learning programs to support children's developmental readiness.